Implementasi Prinsip Isi dan Kualitas pada Laporan Keberlanjutan - Nelson Nelson; Carmel Meiden (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Sustainability report provides an overview of how corporate manages their operations and implementing various efforts towards sustainable and responsible business based on the economy, environment, and social performance according to 17 Sustainable Development Goals. Study case was made to examine development of content and quality principle based on Global Reporting Initiative Standard guidance of sustainability report in company listed on the Indonesia Stock Exhange for the 2018-2020 period. The objects used in this study are PT AKR Corporindo Tbk, PT Indocement Tunggal Prakarsa Tbk, PT Astra International Tbk, and PT Unilever Indonesia Tbk. Nonprobability sampling was carried out and data was collected from official company website. Quantitative and qualitative content analysis approach used in this study. The results of the study case show that based on content principle, the highest quantitative disclosure is materiality aspect and the lowest is stakeholder aspect, the highest qualitative disclosure is sustainability context and the lowest is completeness aspetc. Clarity aspect was the highest disclosure and reliability aspect was the lowest based on quality principle both on quantitative and qualitative. There was positive trend on sustainability report disclosure on public listed company eventhough only 12,67% from total 713 company between 2018-2020 period. Suggestions for further researchers is to be able to include other sector as research object, such as consumer cyclical, infrastructure, property, and technology sectors.